GREENPEACE CAMPAIGN ON THE PURCHASE OF NON-ENVIRONMENTALLY FRIENDLY PRODUCTS - Pratama, Aldi Adi; Bayyinah, Aulia Nabil; Ramadhana, Rakha (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2023)
Introduction: The economic management system is based on the principle of economic actors, tending to focus on the needs, comfort and health of consumers. It is very incomplete, if it is not environmentally oriented when the product is no longer used. The purpose of this study is to find out whether green peace campaigns can influence the choice of non-environmentally friendly products on consumer demand. This research is also expected to be able to make an evaluation for the XYZ company in developing products, based on balancing consumer demand with the environment Methods: The method used in this research is using a closed questionnaire data processing approach, and includes the interview method, in analyzing why the respondent chose a particular answer Results: The selection of product D with non-environmentally friendly packaging and components, still has the highest purchase rate of 1,9. Followed by the second-ranking of product B from the second statement with non-environmentally friendly packaging often purchased at 1,8; the third-ranking product A from the first statement with environmentally friendly packaging is purchased more often at 1,3; and the last ranking of product C from the third statement with environmentally friendly packaging and components is often purchased at 1,2. Conclusion and suggestion: The concept of selecting relatively cheaper costs, is said to still be the main product choice for consumer behavior, even though it has non-environmentally friendly risks. Data processing also shows that the selection of environmentally friendly products with more expensive costs is less chosen by consumers.